Lenalidomide reduces survival of chronic lymphocytic leukemia cells in primary cocultures by altering the myeloid microenvironment - Schulz, Angela; Dürr, Claudia; Zenz, Thorsten; Döhner, Hartmut; Stilgenbauer, Stephan; Lichter, Peter; Seiffert, Martina (Blood, 2013)
Chronic lymphocytic leukemia (CLL) cells depend on microenvironmental stimuli for their survival, provided for example by monocyte-derived nurse-like cells (NLCs). The immunomodulatory drug lenalidomide shows therapeutic effects in subgroups of CLL patients, and is believed to act via the microenvironment. To investigate the effects of lenalidomide on the survival support of NLCs, cocultures of monocytes and CLL cells were treated for 14 days with lenalidomide, which resulted in significantly decreased viability of CLL cells. Among the changes induced by this drug, we observed reduced expression of HLA-DR in NLCs as well as increased secretion of interleukin-10 (IL-10), indicating an altered inflammatory milieu in the cocultures. The increase in IL-10 levels lead to an induction of STAT1 phosphorylation in CLL cells and to enhanced cell-surface expression of intercellular adhesion molecule 1 and altered expression of cytoskeletal and migration-related genes. Chemotaxis assays with lenalidomide-treated CLL cells revealed an impaired migration capability. Our data show that lenalidomide reduces the survival support of NLCs for CLL cells in vitro, suggesting that this drug affects the myeloid microenvironment in CLL in vivo. Furthermore, lenalidomide acts on the migratory potential of CLL cells, which may affect circulation and homing of CLL cells in vivo.